STUDI KOMPARATIF TENTANG SYIBHUL ‘IDDAH BAGI LAKI-LAKI ANTARA HUKUM ISLAM DAN KOMPILASI HUKUM ISLAM - NIM. A1011211135, NARATAMA RIZKI PUTRA (Jurnal Fatwa Hukum, 2026)
Abstract This study is motivated by unequal treatment between men and women in the application of ‘iddah within Islamic law. Classical Islamic jurisprudence generally imposes the obligation of ‘iddah solely on women, while men are not subject to any waiting period after divorce. However, several contemporary scholars, including Wahbah az-Zuhaili, have introduced the concept of syibhul ‘iddah for men under certain conditions, such as the prohibition of marrying women who are closely related to a former wife or when a man has already reached the maximum number of four wives. This study aims to examine the similarities and differences in the concept of syibhul ‘iddah for men between Islamic law and the Compilation of Islamic Law (KHI), as well as to analyze the strengths and weaknesses of its regulation in both legal systems. This research employs a qualitative method with a normative legal approach. It is descriptive-comparative in nature and applies statutory, conceptual, and comparative approaches. Data are collected through library research by examining primary legal sources and relevant secondary literature. The findings indicate that both Islamic law and the KHI recognize the existence of a waiting period for men after divorce before remarrying, which serves to preserve public welfare (maṣlaḥah), prevent lineage ambiguity, and protect women’s rights. Islamic law conceptualizes syibhul ‘iddah as a normative-theological doctrine derived from scholarly ijtihād, emphasizing moral awareness and individual responsibility. While this approach offers ethical flexibility, it lacks legal certainty and administrative enforceability. In contrast, the KHI regulates syibhul ‘iddah through binding written legal norms supported by institutional mechanisms such as the Religious Courts and the Office of Religious Affairs, thereby ensuring legal certainty and juridical protection for women and children, although it places greater emphasis on legal-formal aspects than on moral and spiritual dimensions. Overall, the study concludes that both legal systems are complementary in promoting justice and order within Islamic family law in Indonesia. Keywords: compilation of islamic law, islamic law, syibh al-‘iddah   Abstrak Penelitian ini dilatarbelakangi oleh adanya perbedaan perlakuan antara laki-laki dan perempuan dalam pelaksanaan ‘iddah dalam hukum Islam. Dalam fikih klasik, kewajiban ‘iddah hanya dibebankan kepada perempuan, sementara laki-laki tidak dikenai masa tunggu. Namun, sejumlah ulama kontemporer, seperti Wahbah az-Zuhaili, mengemukakan adanya kondisi tertentu yang menyerupai syibhul ‘iddah bagi laki-laki, antara lain larangan menikahi perempuan yang memiliki hubungan mahram dengan mantan istri atau ketika laki-laki telah memiliki empat istri. Berdasarkan hal tersebut, penelitian ini mengkaji persamaan dan perbedaan konsep syibhul ‘iddah bagi laki-laki antara hukum Islam dan Kompilasi Hukum Islam (KHI), serta menganalisis kelebihan dan kekurangannya dalam kedua sistem hukum tersebut. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan normatif. Penelitian ini bersifat deskriptif-komparatif dengan menggunakan pendekatan perundang-undangan, konseptual, dan perbandingan. Teknik pengumpulan data dilakukan melalui studi kepustakaan dengan menelaah sumber-sumber primer dan literatur sekunder yang relevan dengan tema penelitian. Hasil penelitian menunjukkan bahwa hukum Islam dan Kompilasi Hukum Islam sama-sama mengakui adanya masa tunggu bagi laki-laki pasca perceraian sebelum menikah kembali, dengan tujuan menjaga kemaslahatan, mencegah kerancuan nasab, dan melindungi hak-hak perempuan. Hukum Islam memandang syibhul ‘iddah sebagai konsep normatif-teologis yang bersumber dari ijtihad ulama dan menekankan kesadaran moral serta tanggung jawab individual, sehingga bersifat fleksibel namun lemah dalam aspek kepastian hukum dan administrasi. Sebaliknya, KHI mengatur syibhul ‘iddah secara formal dan mengikat melalui mekanisme kelembagaan, sehingga memberikan kepastian hukum dan perlindungan yuridis, meskipun cenderung menitikberatkan pada aspek legal-formal. Temuan ini menegaskan bahwa kedua sistem hukum tersebut bersifat saling melengkapi dalam mewujudkan keadilan dan ketertiban hukum keluarga Islam di Indonesia. Kata kunci: hukum islam, kompilasi hukum islam, syibhul ‘iddah